2004
DOI: 10.1144/1470-9236/04-007
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical head decay in closed basin aquifers: an insight into fossil groundwater and recharge events in the Andes of northern Chile

Abstract: Many small to moderate-sized, closed aquifer basins in northern Chile show a groundwater gradient indicating flow despite an apparent lack of recharge under current climatic conditions. An examination of the mechanisms that might produce such flow suggests that the only realistic possibility is head decay from an earlier higher water level caused by ancient recharge. Model studies suggest that for small basins, such recharge must have taken place within the last 1000 years and possibly within the last few hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…Studying deposits formed during these wet periods is a first step towards assessing water runoff and replenishment of groundwater reserves (Houston and Hart, 2004;Herrera and Custodio, 2014). These pluvial events were also vital to human subsistence following the initial occupation of the region between 11.5 and 13 ka ago (Moreno et al, 2009;Santoro et al, 2011;Gay o et al, 2015) as well as the last two centuries when water needs for mining, agriculture and human consumption have greatly increased.…”
Section: Introductionmentioning
confidence: 99%
“…Studying deposits formed during these wet periods is a first step towards assessing water runoff and replenishment of groundwater reserves (Houston and Hart, 2004;Herrera and Custodio, 2014). These pluvial events were also vital to human subsistence following the initial occupation of the region between 11.5 and 13 ka ago (Moreno et al, 2009;Santoro et al, 2011;Gay o et al, 2015) as well as the last two centuries when water needs for mining, agriculture and human consumption have greatly increased.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, Stimson et al (1996) show that 3 H can be used to identify recharge and flow paths in phreatic Andean aquifers. Furthermore, Houston and Hart (2004) have shown that many small Andean basins contain groundwater that must receive intermittent recharge in order to maintain gradients and playa evaporation. The chloride (Cl) mass balance technique (Allison and Hughes, 1978;Dettinger, 1989) has been shown to provide an additional approach to the estimation of recharge that has not previously been applied in the Andean Cordillera.…”
Section: Introductionmentioning
confidence: 99%
“…Their compositions (À11& to À9& for d 18 O VSMOW and À90& to À80& for d 2 H VSMOW ) are consistent with recharge in the Andes at elevations around 3500-4000 m (Aravena et al, 1999). Rissmann (2003) suggested that dilute groundwaters in the Monturaqui Basin, proximal to the Andes, may have been recharged at elevations lower than 3500 m during wetter periods in the Pleistocene (54.4-15.3 ka) and short periods in the Holocene (11.4-10.2 and 6.2-3.5 ka) (Bobst et al, 2001) (Houston and Hart, 2004).…”
Section: Groundwater Sourcesmentioning
confidence: 76%
“…The hyperarid climate has reduced the rate of surface erosion to $1 cm/ka since that time (Alpers and Brimhall, 1988). There have been, however, more pluvial periods during this time (Bobst et al, 2001;Houston and Hart, 2004).…”
Section: Geological and Hydrological Settingmentioning
confidence: 99%